Psychosocial Issues Following Natural Disaster in Palu Central Sulawesi: A Case Study on Adolescents - Ike Herdiana; Rahmatsyam Lakoro (Universitas Ahmad Dahlan, 2022)
Earthquakes, tsunami, and soil liquefaction struck Palu, Central Sulawesi on September 28th, 2018. This study case aims to identify psychosocial issues among adolescents following the devastating disaster. Qualitative data were collected through in-depth interviews with five survivors aged 16 to 17 years old. Participants reported trauma, anxiety, and grief. Nonetheless, they developed positive coping mechanisms to help them adapt to post-disaster situations. Families contributed by providing a safe and comfortable space, while schools played role in delivering post-disaster education. The findings imply that a psychosocial intervention needs to be developed for adolescents who are to this day still struggling with the psychological consequences of the natural catastrophe.